Standards for Studies of Neurological Prognostication in Comatose Survivors of Cardiac Arrest: A Scientific Statement From the American Heart Association. Issue 9 (27th August 2019) - Geocadin, Romergryko G.; Callaway, Clifton W.; Fink, Ericka L.; Golan, Eyal; Greer, David M.; Ko, Nerissa U.; Lang, Eddy; Licht, Daniel J.; Marino, Bradley S.; McNair, Norma D.; Peberdy, Mary Ann; Perman, Sarah M.; et al.
Abstract : Significant improvements have been achieved in cardiac arrest resuscitation and postarrest resuscitation care, but mortality remains high. Most of the poor outcomes and deaths of cardiac arrest survivors have been attributed to widespread brain injury. This brain injury, commonly manifested as a comatose state, is a marker of poor outcome and a major basis for unfavorable neurological prognostication. Accurate prognostication is important to avoid pursuing futile treatments when poor outcome is inevitable but also to avoid an inappropriate withdrawal of life-sustaining treatment in patients who may otherwise have a chance of achieving meaningful neurological recovery. Inaccurate neurological prognostication leading to withdrawal of life-sustaining treatment and deaths may significantly bias clinical studies, leading to failure in detecting the true study outcomes. The American Heart Association Emergency Cardiovascular Care Science Subcommittee organized a writing group composed of adult and pediatric experts from neurology, cardiology, emergency medicine, intensive care medicine, and nursing to review existing neurological prognostication studies, the practice of neurological prognostication, and withdrawal of life-sustaining treatment. The writing group determined that the overall quality of existing neurological prognostication studies is low. As a consequence, the degree of confidence in the predictors and the subsequent outcomes is also low. Therefore, the writing group suggests that neurological prognostication parameters need to be approached as index tests based on relevant neurological functions that are directly related to the functional outcome and contribute to the quality of life of cardiac arrest survivors. Suggestions to improve the quality of adult and pediatric neurological prognostication studies are provided.